Diversity Management nuove frontiere dell'inclusione e sfide per i C.U.G. universitari - Francesca Galgano (Cultura delle differenze: Diritto, conoscenza, formazione, 2020)
Another step of the Trotula Project created by the University Federico II's Equal Opportunity Committee: In December 2019, the National Congress brought together the University Equal Opportunity Committees from all over Italy. Now we are publishing the Transcripts in a period of the COVID-19 emergency, during which Diversity has appeared as a crucial theme. We know it is just a little step on a long path, but we are happy to introduce many significant, sensitive and passionate voices of a mindful Community that dialogues with its territory on culture of differences today and while thinking to the future.